Investigation of structural and electrical properties on substrate material for high frequency metal–oxide–semiconductor (MOS) devices. (21st April 2017) - Kumar, M; Yang, Sung-Hyun; Janardhan Reddy, K; JagadeeshChandra, S V
Abstract: Hafnium oxide (HfO2 ) thin films were grown on cleaned P-type ⟨1 0 0⟩ Ge and Si substrates by using atomic layer deposition technique (ALD) with thickness of 8 nm. The composition analysis of as-deposited and annealed HfO2 films was characterized by XPS, further electrical measurements; we fabricated the metal–oxide–semiconductor (MOS) devices with Pt electrode. Post deposition annealing in O2 ambient at 500 °C for 30 min was carried out on both Ge and Si devices. Capacitance–voltage ( C – V ) and conductance–voltage ( G – V ) curves measured at 1 MHz. The Ge MOS devices showed improved interfacial and electrical properties, high dielectric constant ( 19), smaller EOT value (0.7 nm), and smaller D it value as Si MOS devices. The C – V curves shown significantly high accumulation capacitance values from Ge devices, relatively when compare with the Si MOS devices before and after annealing. It could be due to the presence of very thin interfacial layer at HfO2 /Ge stacks than HfO2 /Si stacks conformed by the HRTEM images. Besides, from current–voltage ( I – V ) curves of the Ge devices exhibited similar leakage current as Si devices. Therefore, Ge might be a reliable substrate material for structural, electrical and high frequency applications.